‘Sovereignty’ over submerged cultural heritage in the Canadian Arctic waters : case study from the Franklin expedition wrecks (1845-48) - Lasserre, Frédéric; Pelletier, Sébastien; Têtu, Pierre-Louis; Dawson, Jackie (Polar Geography, 2019)
Transiting the Northwest Passage captured the imaginations of explorers and adventures for centuries. The idea of a shorter and more economical trade route through the frozen North resulted in hundreds of state and privately financed expeditions to the Canadian Arctic. Perhaps the most famous of the expeditions was the British-led Franklin voyage including the HMS Erebus and HMS Terror, which in April 1848 became stuck in ice and were abandoned in the Victoria Strait. Dozens of expeditions were subsequently commissioned to find the ships, but they would not be seen again until more than 150 years later when their wrecks were found on the sea floor of the Canadian Arctic. Despite the recent transfer of ownership of Franklin’s shipwrecks by the British to the Canadian Government, this case study illustrates the complexity of the identification of ownership over shipwrecks. Based on a literature review of international legal frameworks regarding submerged cultural heritage, claims and statements of various perspectives are documented. In a context of increasing marine tourism activity, in particular pleasure craft traffic, in the Canadian Arctic, efforts must be made to ensure nothing ends up in the hands of looters and private collectors who trade them on the black market.